Education, Modern Development, and Indigenous Knowledge - McGovern, Seana (Routledge, 2013)
This book re-conceptualizes the field of international and comparative education by utilizing indigenous knowledge as a central component for altering the dominant, eurocentric social science research paradigm. Examples from indigenous sources of knowledge are juxtaposed to the dominant discourses on education and modern development in subaltern societies in order to provide scholars with alternative ways of viewing education and development and to shape how subaltern peoples are understood and represented in academic research. Bibliography. Index.